The experience of an indipendent center with the MINIHIP® femoral stem - Giaretta, Stefano; Ambrosini, Carlo; Lunardelli, Enrico; Barison, Elia; Momoli, Alberto (Acta Biomedica Atenei Parmensis, 2022)
The implantation of short femoral stems has significantly increased over the past decade, thanks to their preservation of bone stock, allowing for easier potential revision of components and physiological joint reconstruction. Their main features are metaphyseal fixation and partial retention of the femoral neck which lead to biomechanical advantages and high stability. They also guarantee the preservation of bone stock and insertion through minimally invasive approaches. Fifty-one non-consecutive patients with osteoarthritis or avascular necrosis were treated by two senior surgeons with total hip arthroplasty (THA) with anterior or anterolateral approach between April 2013 and October 2016. Cementless short femoral stem monobloc (Minihip, Corin, Cirencester, UK) was implanted in all patients who were studied retrospectively. Radiographic outcome was analyzed and clinical outcomes were assessed with Harris Hip Score (HHS), Hip handicap and Osteaorthritis Outcome Score (HOOS) and Oxford Hip Score (OHS). Based on radiological results we did not find periprosthetic osteolysis while bone resorption was evaluated in 5 implants which were classified according to Gruen. The MiniHip stem demonstrates adequate metaphyseal grip, excellent implant stability to ensure implant survival